2020
DOI: 10.1080/1331677x.2020.1748507
|View full text |Cite
|
Sign up to set email alerts
|

Population ageing, labour productivity and economic welfare in the European Union

Abstract: This paper examines the impact of the ageing dimensions and other economic and social variables on labour productivity and poverty risk within the European Union (EU). Taking into account the sizable dissimilarities among the EU Member States, our research is configured on four specific panels, according to the UNECE/European Commission mapping of EU countries, based on the Active Ageing Index data and methodology for 2018. We have compiled a complex dataset with official data to measure the ageing features, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
3
22
0
1
Order By: Relevance
“…In order to restrain the unfavorable impact over labor productivity, authors [11] (p. 18) highlighted "the crucial role played by labor market reforms such as increases in active labor market policies on training or increase in the availability of medical inputs" and also older employees' training and innovation. Cristea et al [5] deepen the analysis of the influence of employees aged 55-64 years on labor productivity on the four groups of EU countries, according to the AAI scores. Authors [5] showed that, within countries with the lowest AAI results, the ageing workforce (55-64 years) induce a downsized labor productivity, while for the other countries, with higher AAI scores, the effects are favorable.…”
Section: State Of the Arts On The Ageing Phenomenon And Labor Market Integration Within The Economic Welfare Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to restrain the unfavorable impact over labor productivity, authors [11] (p. 18) highlighted "the crucial role played by labor market reforms such as increases in active labor market policies on training or increase in the availability of medical inputs" and also older employees' training and innovation. Cristea et al [5] deepen the analysis of the influence of employees aged 55-64 years on labor productivity on the four groups of EU countries, according to the AAI scores. Authors [5] showed that, within countries with the lowest AAI results, the ageing workforce (55-64 years) induce a downsized labor productivity, while for the other countries, with higher AAI scores, the effects are favorable.…”
Section: State Of the Arts On The Ageing Phenomenon And Labor Market Integration Within The Economic Welfare Contextmentioning
confidence: 99%
“…Cristea et al [5] deepen the analysis of the influence of employees aged 55-64 years on labor productivity on the four groups of EU countries, according to the AAI scores. Authors [5] showed that, within countries with the lowest AAI results, the ageing workforce (55-64 years) induce a downsized labor productivity, while for the other countries, with higher AAI scores, the effects are favorable.…”
Section: State Of the Arts On The Ageing Phenomenon And Labor Market Integration Within The Economic Welfare Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…The ratio of people living below the poverty line has been calculated by income distribution (Cuaresma et al, 2018), household income (Lázár et al, 2020), household consumption (Ahmed et al, 2018), and growth of gross domestic product (GDP) (Ashimov et al, 2019;Ndhleve et al, 2017). Some models estimated poverty rates based on labor productivities and education levels (Cristea et al, 2020) or ecological factors such as topography, rainfall, and desertification (Zhou et al, 2020). The poverty population indicator is similar to the poverty rate, which is defined as the number of people living below a given poverty line.…”
Section: Overview Of Model Informationmentioning
confidence: 99%